NYUMPAH: UNGKAPAN KEMARAHAN DALAM MASYARAKAT MELAYU PONTIANAK KALIMANTAN BARAT - Syarifah Lubna (Balai Bahasa Kalimantan Barat, 2019)
As the uniqueness of each language, the expression of anger is also something unique and peculiar which is expressed differently depending on the culture of each community, including the society of Pontianak Malay Kalimantan Barat. In connection with this peculiarity, since childhood or nowadays the society of Pontianak Malay Kalimantan Barat do not only reflect dislike, disapproval of things and differences of opinion or understanding through anger, but more than that the expressions of anger also shows caring and closeness in the closest environment such as family and daily interactions. There are various expressions of anger in the society of Pontianak Malay Kalimantan Barat including nyumpah. Nyumpah is the focus and aim of the research to be described qualitatively. The research sample was 100 respondents selected randomly from the total population of the society of Pontianak Malay Kalimantan Barat. This study applied descriptive statistics. The data collected and disseminated through questionnaires and analyzed through tabulation of statistical product and service solution (SPSS) based on the Likert scale which are: strongly disagree (1), disagree (2), doubtful (3), agree (4), and strongly agree (5). Based on the data, it could be concluded that society of Pontianak Malay not expressing their anger through nyumpah in the closest social environment and family (66% of respondents not agree and even strongly not agree).